A precise view of big data based analysis on various parameters under the field of gaming analytics - Udaya Nirmala Mary, R.; Nandhini, R. (International Journal of Engineering and Technology, 2017)
Big data and analytics has brought revolutions in many of the fields. Gaming is one such field. Analytics is being implemented in games to classify the user and predict their behaviors. These techniques require some basic survey on gaming and analytics. This article is such an approach to game analytics focusing on its origin, causes, effects and machine learning techniques used in game analytics. This survey provides a better understanding about game analytics and the publications related to it.